Konsep Stoisisme Untuk Mengatasi Emosi Negatif Menurut Henry Manampiring - Fitri, Hartika Utami; Syarifuddin, Achmad; Mayasari, Ayu (Kuras Institute, 2021)
Emosional management skills are improtant because they have a greater contribution to a person’s succes than intellectual intelligence. Good emotional management concerns how individuals are able to understand the feelings of others and themselves so that they can put themselves in the right position and behave well towards themselves and others. This is relevant to today’s life which is full of uncertainty such as many individual hoaxes. The purpose of this researchis to describe how the consept of Stoicism according to Henry Manampiring and describing circulating on social media that can cause negative emotions in the method with a descriptive approach anda data collection in the form of documentation. Stoicism is a concept which by its essence amor fati frees oneself from this sense of dependence anda anxiety taht is not used properly it will cause negative emotions, dependence and excessive worry. The results show that the stoicism concept is effective in evercoming negative emotions as contained in the core philosophy book by applying the control dichotomy, control trichotomy, and can also use the S-T-A-R steps. Or it could be by transferring emotions the way is kartasis, rationalization and contemplation. Then, cognitive adjustment in the form of cognitive attribution and empathy, then coping how to use Stoicism concept to overcome negative emotions. For our qualitative method on the use of the control dichotomy. Reasoning or contol applies a trichoyomy. Understanding and seita occurs in the strategy sena in the form of emotional and problem focused coping .